A Case of Fungemia Caused by Postoperative Chronic Lumbar Intervertebral Disc Infection. (8th August 2022) - Zheng, Rui; Jin, Taicheng; Tao, Rui; Xu, Ning
Abstract : Postoperative surgical site infection is one of the serious postoperative complications of spine surgery, especially fungal infections. Late-stage surgical site fungal infections often lack typical clinical symptoms and have a variable clinical presentation. In this case, the patient was a senior patient with usually only tolerable pain and discomfort, which was detected 2 years after the first surgery. Such cases are even rarer for fungal bloodstream infections caused by delayed postoperative chronic fungal osteomyelitis and deserve further study for early identification and intervention to minimize harm.